De novo KCNA6 variants with attenuated KV1.6 channel deactivation in patients with epilepsy. Issue 2 (5th December 2022) - Salpietro, Vincenzo; Galassi Deforie, Valentina; Efthymiou, Stephanie; O'Connor, Emer; Marcé‐Grau, Anna; Maroofian, Reza; Striano, Pasquale; Zara, Federico; Morrow, Michelle M.; ,; Reich, Adi; Blevins, Amy; et al.
Abstract: Objective: Mutations in the genes encoding neuronal ion channels are a common cause of Mendelian neurological diseases. We sought to identify novel de novo sequence variants in cases with early infantile epileptic phenotypes and neurodevelopmental anomalies. Methods: Following clinical diagnosis, we performed whole exome sequencing of the index cases and their parents. Identified channel variants were expressed in Xenopus oocytes and their functional properties assessed using two‐electrode voltage clamp. Results: We identified novel de novo variants in KCNA6 in four unrelated individuals variably affected with neurodevelopmental disorders and seizures with onset in the first year of life. Three of the four identified mutations affect the pore‐lining S6 α‐helix of KV 1.6. A prominent finding of functional characterization in Xenopus oocytes was that the channel variants showed only minor effects on channel activation but slowed channel closure and shifted the voltage dependence of deactivation in a hyperpolarizing direction. Channels with a mutation affecting the S6 helix display dominant effects on channel deactivation when co‐expressed with wild‐type KV 1.6 or KV 1.1 subunits. Significance: This is the first report of de novo nonsynonymous variants in KCNA6 associated with neurological or any clinical features. Channel variants showed a consistent effect on channel deactivation, slowing the rate of channel closure following normal activation. This specific gain‐of‐function feature is likely to underlie the neurological phenotype in our patients. Our data highlight KCNA6 as a novel channelopathy gene associated with early infantile epileptic phenotypes and neurodevelopmental anomalies.